Discussion Remarks on the Role of Wood and Chitin Constituents during Carbonization - Ilnicka, Anna; Lukaszewicz, Jerzy P. (Frontiers in Materials, 2015)
Nature is a source of some biomaterials like wood and chitin which can be successfully transformed into chars of advanced structural/surface parameters. The manuscript is discursive and suggests that particular components of the materials (cellulose, lignin, hemicellulose, alfa-chitin fibrils, mineral-protein matrix) play a specific role in the manufacturing of porous chars. It is proposed that some of the components (hemicellulose and mineral-protein matrixes) behave like a natural soft template during carbonization of wood and chitin. It is suggested why particular components and derivatives of wood and chitin (cellulose and chitosan) can not form porous carbonaceous matrixes when are carbonized separately.